3D Printing of Photocrosslinked Alginate Dialdehyde-Gelatin Hydrogels Reinforced with Cobalt-Containing Mesoporous Bioactive Glass Nanoparticles for Developing Skin Wound Dressings - Zeimaran, Ehsan; Pourshahrestani, Sara; Röder, Jonas; Detsch, Rainer; Boccaccini, Aldo R. (Advanced Materials Interfaces, 2025)
Designing three-dimensional (3D)-printable hydrogels presents a significant challenge, particularly in maintaining the polymer concentration at minimal levels while ensuring that the printing process can be cell-friendly at room temperature. This study aims to examine the feasibility of designing multi-crosslinked hydrogels composed of methacrylate-functionalized alginate dialdehyde (ADAMA) and different concentrations of gelatin methacrylate (GelMA). Cobalt-doped mesoporous bioactive glass nanoparticles (Co-MBGNs) are incorporated into the hydrogels to further tailor their mechanical and biological properties. The hydrogels, crosslinked under UV and immersed in calcium chloride solution, show high elasticity and fatigue resistance over five compression cycles. The inclusion of Co-MBGNs enhances the mechanical properties while cell viability is higher in the pure polymeric hydrogels. The nanocomposites promote cell aggregate formation. The non-cytotoxic hydrogel supernatants induce NHDF cell migration at rates similar to or even faster than the control group. The printability of hydrogels is also examined through extrusion-bioprinting approach. The room-temperature printing is only possible for the hydrogels made of 5 wt% of GelMA and 2.5 wt% of ADAMA. The 3D-printed constructs show impressive elasticity and are easy to handle. These findings can offer valuable insights into the development of mechanically robust and customizable wound dressings.
CRIS-Team Scopus Importer:2025-04-11
Keywords: GelMA; mesoporous bioactive glass nanoparticles; methacrylated alginate dialdehyde; printable hydrogels; wound healing